Lampu Taman Tenaga Surya Berbasis Internet Of Things di Universitas Bangka Belitung - Dwi Haryanto, Anggara; Asmar, Asmar; Hendrawan Budianto, Tri; Sunanda, Wahri (Jurusan Teknik Elektro Fakultas Teknik Universitas Bangka Belitung, 2022)
Universitas Bangka Belitung has a solar power plant as an alternative energy source, some of which function as an energy source for garden lights. Garden lighting using led lights is an alternative to illuminating the Universitas Bangka Belitung. In an effort to overcome deficiencies in manual monitoring, innovation is needed in controlling solar garden lights using the Internet of Things (IoT). From the measurement results on garden lights, the average voltage value based on sensor measurements is 14.39 V, the average current is 0.81 A, and the average power is 11.65W. For measurement conditions based on a multimeter, the average voltage value is 13.41 V, the average current value is 0.76 A, and the average real power value is 10.19 W.